Clean Water Supply in Tasikmalaya Municipality, Opportunities and Challenges - Sulwan Permana; Adi Susetyaningsih; Dicky Muhamad Fadli (Journal of Geoscience, Engineering, Environment, and Technology, 2022)
Currently, there are three sub-districts in Tasikmalaya City that are still vulnerable to clean water, namely Kawalu, Tamansari, and Cibeureum sub-districts. PDAM Tirta Sukapura, owned by the Tasikmalaya Regency Government, has not been able to meet clean water needs, so the Tasikmalaya Municipality Government plans to build a new PDAM as an alternative. The Ciwulan river in Cibeuti Village is a source of water that will be used as a collection point. Rain data was taken from 2 stations, namely Gunung Satria and Cikunten II stations, for ten years. The evapotranspiration value was calculated using the Penman-Monteith method. The calculation of the discharge in the intake area, namely Ciwulan-Cibeuti with a watershed area of ​​405 km2, used the NRECA method using parameters taken from the calibrated Ciwulan-Sukaraja station. The calibration parameters are PSUB = 0.86; GWF = 0.22, reduction coefficient = 0.80; and NSE = 0.764. The determination of the dependable flow is calculated using the Weibull method. The magnitude of the Q90's dependable flow is 4.3 m3/s. The projected population for the next 15 years is estimated at 307,857 people, so the amount of water needed is around 0.535 m3/s. Opportunities for business entities to participate in building PDAM are wide open, with the certainty of return plus profits or independent management by business entities within a certain period of time. The challenge for the government and business entities is to provide reasonable prices to customers and new networks.